Wypalenie szkolne, charakterystyka zjawiska - wzrastające zagrożenie w edukacji = School burnout, characteristics of the phenomenon - a growing threat in education - Góralewska-Słońska, Anna Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article delves into the phenomenon of school burnout, akin to job burnout but experienced by persons during one?s education, rather than in work setting. Justifying this comparison is the shared presence of comparable traits: the need for motivation and active engagement, and, notably, the potential to induce significant stress. School burnout, alternately known as student or pupil burnout, bears a resemblance to occupational counterpart and its complex arises from a multitude reasons. Amongst intrapersonal conditions contributing to student burnout, one can identify low level of cognitive functions, psychopathy, low self-esteem, insufficient stress management and coping skills. Interpersonal contributors include parental pressure, lack of teacher support, conflicts with other students. There also are organizational contributors, including heavy and/or enduring workload, excessively high standards, improper teaching methods.
Keywords: wypalenie szkolne; przyczyny i skutki wypalenia szkolnego; burnout; school burnout; causes and consequences of school burnout